Optimization of Cable Force Adjustment in Cable-Stayed Bridge considering the Number of Stay Cable Adjustment - Han-Hao Zhang; Nan-Nan Sun; Pei-Zhi Wang; Man-Hui Liu; Yuan Li (Advances in Civil Engineering)
Modern cable-stayed bridges are spatial, multicable systems. The cable force needs to be adjusted during the construction phase and maintenance phase. The existing calculation methods of cable force adjustment mainly considered the rationality of structural force, but only few research studies have been conducted on how to reduce the number of stay cables which need to be adjusted. This study aims to propose an optimization calculation method including the optimization module with the sensitivity analysis and updating design variable module (UDVM), which are used for cable force adjustment in cable-stayed bridges. Based on the finite difference method, the sensitivity analysis is adopted in the optimization module, which can capture the response of structures as design variables vary; the particle swarm optimization method is adopted for structural optimization. The proposed method can dramatically reduce the number of stay cables which need to be adjusted and ensure the main girder stresses remain in a reasonable state during stay cable adjustment progress by UDVM. Moreover, the proposed method can continuously update the objective function, constraint conditions, and design variables. Finally, this proposed optimization calculation method is applied to two different cable-stayed bridges to validate the reliability and feasibility of the method.